(untitled) (Journal of Asian Development Studies, 2025)
In this study, we investigate Zipf’s Law, along with Pareto and Power Law distributions, which are often observed in situations where a small number of events dominate while the majority occur less frequently, resulting in a right-skewed distribution. Human population distribution across cities frequently follows this pattern. Using data from the 2017 Population Census, we analyze the population distribution of cities in Khyber Pakhtunkhwa, Pakistan, to test the validity of Zipf’s Law. The results reveal that the population distribution of cities in the province closely adheres to Zipf’s Law. We attribute this conformity to the cohesive nature of the urban system in Khyber Pakhtunkhwa, where common cultural background, shared language, and consistent administrative structures contribute to the observed population hierarchy. These findings highlight the importance of Zipf’s Law as a useful framework for understanding regional urbanization patterns. Moreover, the study provides a foundation for future research on city-size distributions and urban planning policies in Pakistan.